The Ability of the Elderly to Follow PROLANIS (Chronic Disease Management Program) Exercise Movements - Duwi PudjiAstuti; Suryanti Suryanti; Satino Satino (Journal Keperawatan, 2025)
Background: Over the past five years, the proportion of the elderly population in Indonesia has continued to increase to 12%. The government's efforts to support the health of seniors with chronic diseases include the PROLANIS (Chronic Disease Management Program), which includes structured Exercise Movements to help participants maintain their physical condition and manage their illnesses. As older adults age, they experience a decline in bodily functions, which can impact physical activity limitations, including exercise. Purpose: To determine the ability of the elderly to carry out PROLANIS exercises at Puskesmas Sibela Surakarta. Methods: This research is a quantitative study using descriptive methods. The study population was all PROLANIS participants, with a sample of 46 respondents selected based on inclusion criteria: participants registered with PROLANIS program at Puskesmas Sibela Surakarta and participating in exercise movements activities twice a month for 20 minutes. The instrument used was an observation sheet containing the ability of elderly people to participate in exercise movements. Results: All elderly people routinely do PROLANIS exercises twice a month and the majority of elderly people are able to participate in the exercise movements as a whole, namely 41 people (89.1%) in the first and second meetings. Conclusion: The majority of elderly PROLANIS participants at Puskesmas Sibela Surakarta were able to complete the entire exercise movements routine at both sessions. This demonstrates that PROLANIS exercise movements can be successfully performed by elderly individuals despite the decline in bodily functions due to aging.